Impact of Explanation on Sense of Control and Perceived Power Relationship Towards Online Advisory System - Asiah, Asmuni (2012)
Online advisory services have become ubiquitous and are of the essence of life in today’s living. Many government agencies these days are offering such services as a means to provide a hassle free assistance to the public in fulfilling their information and service needs. This project assesses the impact of providing online advisory services, in particular those with explanation feature, to the public. Building on insights from practice and literature, the project utilizes a survey to empirically examine the key role of explanation feature provided in online advisory tools. Three online advisory tools being examined are the e-Filing, e-Quit Rent and e-Assessment; all provide services related to tax assessment. 100 respondents involved in this small scale project; their opinions are gathered by means of questionnaire which is developed from four major constructs namely information process satisfaction, information process transparency, sense of control and perceived power relationship. The analysis phase involved the use of SPSS version 19.0 that supports various data analysis techniques including descriptive statistics, cross tabulation and correlation. The findings reveal fore-Filing shows sense of control lead to greater satisfaction among public. Whilee-Quit Rentande-Assessment is the perceived power relationship is better for the satisfaction of information. For transparency in the process of e-filing information ande-Quit Rent, a sense of control is better than the perceived power relationship in steadofe-Assessment. It can be concluded from this project that the explanation in online advisory tools gives the public a better sense of control over their assessment outcome. It also gives the public a better perceived power relationship with the government agency to which they are beholden.